SECRETIVE SECRETIONS, EXPLOSIVE EXCRETIONS: A RARE CASE OF VIPoma - Ng, Sim Yin; Chiew, Ken Seng (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Vasoactive Intestinal Peptide (VIP)-secreting neuroendo- crine tumours (VIPomas) are rare, usually presenting with profuse watery diarrhea leading to severe electrolyte imbalances. Our patient’s initial presentation with obstructive jaundice and portal vein thrombosis preceded the typical presentation, complicating early diagnosis. CASE A 34-year-old male presented in May 2024 with progressive jaundice, tea-colored urine and pale stools but no diarrhea. Investigations revealed markedly elevated direct hyperbilirubinemia (205 µmol/L), alkaline phosphatase (742 U/L) and gamma-glutamyl transferase (612 U/L), which was suggestive of biliary obstruction. CT scan identified a 4.2 cm pancreatic mass with hepatic metastases and portal vein thrombosis. EUS visualized a hypoechoic lesion at the head of the pancreas measuring 38 x 35 mm, causing upstream dilatation of the pancreatic and common bile duct. ERCP was done for sphincterectomy and stenting. Histopathology revealed a low-grade neuroendocrine neoplasm. Six months later, the patient developed persistent watery diarrhea for two weeks, along with fatigue and weight loss. His severe hypokalemia (as low as 1.5 mmol/L) was refractory despite 3 days of intravenous potassium infusion. Stool studies excluded infective causes, and 24-hour urine 5-HIAA was normal. Trial of subcutaneous octreotide, titrated up to 100 mcg, led to resolution of symptoms and hypokalaemia within a day. His fasting serum VIP levels sent prior to initiation of therapy were elevated at 211 pg/ml (normal range <86 pg/ mL). Gallium-68 DOTATATE showed somatostatin-avid disease at the pancreatic head, multiple abdominopelvic lymph nodes and both liver lobes. Our multidisciplinary team meeting determined that curative surgery was not feasible due to extensive metastases and vascular involvement. The patient remains well and asymptomatic on octreotide long-acting release during subsequent follow-ups. CONCLUSION This case highlights an unusual case of VIPoma, which presented with cholestatic jaundice prior to diarrhea. Strong multidisciplinary collaboration is crucial to optimize outcomes.